2011
DOI: 10.1002/ijc.25829
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol‐3′‐kinase/AKT signaling is essential in synovial sarcoma

Abstract: Synovial sarcomas account for 5-10% of all malignant soft tissue tumors. They have been shown to express different membranous growth factor receptors, many of them signaling via intracellular kinase cascades. In our study, the functional role of PI3K/AKT signals in synovial sarcoma is analyzed with regard to tumor biology and therapeutic applicability. Immunohistochemical stainings of (Ser473)-phosphorylated (p)-AKT, its targets p-(Ser9)-GSK-3b and p-(Ser2448)-mTOR and the cell cycle regulators Cyclin D1 and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 48 publications
3
31
0
Order By: Relevance
“…This epithelioiddominant staining pattern was mentioned in a previous study. 5 However, its significance remains unclear, because this pattern had no correlation with other clinicopathologic parameters in the current study. Patients who had pAkt-positive tumors had a better clinical response to chemotherapy than those who had tumors that were negative for pAkt, and this tendency was not observed for the other molecular markers.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…This epithelioiddominant staining pattern was mentioned in a previous study. 5 However, its significance remains unclear, because this pattern had no correlation with other clinicopathologic parameters in the current study. Patients who had pAkt-positive tumors had a better clinical response to chemotherapy than those who had tumors that were negative for pAkt, and this tendency was not observed for the other molecular markers.…”
Section: Discussionmentioning
confidence: 56%
“…Several previous studies have demonstrated the activation of this pathway and its contribution to cell survival and proliferation in SS in vitro. 3,5 However, the expression profiles of the molecules along the Akt/mTOR pathway have been analyzed in a relatively small number of clinical materials. 5,13,14 Some authors investigated Akt/mTOR pathway involvement in STS series and demonstrated a correlation between Akt activation and a worse prognosis 15 or a greater probability of metastasis 13 ; whereas, to our knowledge, no investigations have focused on SS as a single entity, and the prognostic impact of this pathway on SS has remained to be clarified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that it plays a key role in the inhibition of cell apoptosis and the promotion of cell proliferation by affecting the activation state of a variety of downstream effector molecules. It is closed related to the occurrence and development of many human tumors including hematological malignancies (Xu et al, 2003;Friedrichs et al, 2011;Sun et al, 2011). Akt is a potent kinase for bad as a member of the Bcl-2 family.…”
Section: Discussionmentioning
confidence: 99%